Hadith #2473 - Sunan Abi Dawud - Abdullah bin Budayl al-Khuza'i; Abu Da'ud أبو داود السجستاني الأزدي; Ahmed bin Ibrahim bin Kathir أحمد بن إبراهيم بن كثير; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Umar; Umar ibn al-Khattab (Sunan Abi Dawud)
The sunnah for one who is observing i’tikaf (in a mosque) is not to visit a patient, or to attend a funeral, or touch or embrace one’s wife, or go out for anything but necessary purposes. There is no i’tikaf without fasting, and there is no i’tikaf except in a congregational mosque.
Grade: Hasan Sahih

Hadith #2627 - Sunan Abi Dawud - Abdullah bin al-'Ala' عبد الله بن العلاء بن زبر; al-Waleed bin Muslim bin Shahab الوليد بن مسلم بن شهاب; Amr bin 'Uthman bin Sa'id bin Kahtir عمرو بن عثمان بن سعيد بن كثير; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Muslim bin Mshkm مسلم بن مشكم (Sunan Abi Dawud)
The Prophet (ﷺ) sent a detachment. I gave a sword to a man from among them. When he came back, he said: Would that you saw us how the Messenger of Allah (ﷺ) rebuked us, saying: When I sent out a man who does not fulfil my command, are you unable to appoint in his place one who will fulfil my command.
Grade: Hasan

Hadith #2635 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Jabir ibn 'Abdullah; Sa'id bin Mnswr bin Sh'bh سعيد بن منصور بن شعبة; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) sent us in a detachment and said (to us): If you see a mosque or hear a mu’adhdhin (calling to prayer), do not kill anyone.
Grade: Da'if

Hadith #2649 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Rafi' عبيد الله بن أبي رافع (Sunan Abi Dawud)
Khabbab said “We came to the Apostle of Allaah(ﷺ) while he was reclining on an outer garment in the shade of the Ka’bah. Complaining to him we said “Do you not ask Allaah for help for us? And do you not pray to Allaah for us? He sat aright turning red in his face and said “A man before you (i.e., in ancient times) was caught and a pit was dug for him in the earth and then a saw was brought placed on his head and it was broken into two pieces but that did not turn him away from his rel
Grade: Sahih

Hadith #2767 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Jabir ibn 'Abdullah; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
Hassan ibn Atiyyah said: Makhul and Ibn Zakariyya went to Khalid ibn Ma’dan, and I also went along with them. He reported a tradition on the authority of Jubayr ibn Nufayr. He said: Go with us to Dhu Mikhbar, a man from the Companions of the Prophet (ﷺ). We came to him and Jubayr asked him about peace. He said: I heard the Messenger of Allah (ﷺ) say: You will make a secure peace with the Byzantines, then you and they will fight an enemy behind you.
Grade: Sahih

Hadith #2833 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata' bin Abi Rabah عطاء بن أبي رباح; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Umm Kurz al-Khuza'iyya (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) used to sacrifice goat out of every fifty goats. Abu Dawud said: Fara’ means the first baby camel born (to the Arabs). They used to sacrifice it for their idols, and then eat it, and its skin was thrown on a tree. ‘Atira was a sacrifice made during the first ten days of Rajab.
Grade: Sahih

Hadith #2881 - Sunan Abi Dawud - Ahmed bin Manay' أحمد بن منيع; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ikrama عكرمة; Ruh bin 'Ubada bin al-'Ala' روح بن عبادة بن العلاء; Zakaria bin Ishaq al-Makki زكريا بن إسحاق المكي (Sunan Abi Dawud)
A woman said: Messenger of Allah, my mother suddenly died; if it had not happened, she would have given sadaqah (charity) and donated (something). Will it suffice if I give sadaqah on her behalf? The Prophet (ﷺ) said: Yes, give sadaqah on her behalf.
Grade: Sahih

Hadith #2904 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي (Sunan Abi Dawud)
A man of Khuza’ah died and his estate was brought to the Prophet (ﷺ). He said: Look for his heir or some relative. But they found neither heir nor relative. The Messenger of Allah (ﷺ) said: Give it to the leading man of Khuza’ah. The narrator Yahya said: Sometimes I heard him (al-Husayn ibn Aswad) say in this tradition: Look for the greatest man of Khuza’ah.
Grade: Da'if

Hadith #2913 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad Ibn Maslama; Musa bin Da'ud al-Dby موسى بن داود الضبي أبو عبد الله; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Abi Dawud)
Mu’adh bought the property of a Jew whose heir was a Muslim. He then narrated from the Prophet (ﷺ) to the same effect.
Grade: Da'if

Hadith #2964 - Sunan Abi Dawud - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Malik bin Aws bin al-Hadathan; Sufyan bin 'Uyaynah سفيان بن عيينة; Umar ibn al-Khattab; Uthman bin Muhammad (Sunan Abi Dawud)
They i.e ‘Ali and al-‘Abbas (Allah be pleased with them), were quarrelling about what Allah bestowed on His Messenger of Allah (ﷺ), that is, the property of Banu al-Nadir. Abu Dawud said: He (‘Umar) intended that the name of division should not apply to it.
Grade: Sahih

Hadith #3042 - Sunan Abi Dawud - Amr bin Aws bin Abi Aws عمرو بن أوس بن أبي أوس; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
Ibn ‘Abbas said “When the Prophet of the Persians dies, Iblis (satan) led them to Mazdaism.”
Grade: Hasan

Hadith #3163 - Sunan Abi Dawud - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Jabir ibn 'Abdullah; Muhammad bin Hatm bin Bzy' محمد بن حاتم بن بزيع; Muhammad Ibn Maslama (Sunan Abi Dawud)
I saw the Messenger of Allah (ﷺ) that he kissed Uthman ibn Maz’un while he was dead, and I saw that tears were flowing (from his eyes).
Grade: Sahih

Hadith #3237 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) went out to the graveyard and said: Peace be upon you, inhabitants of the dwellings who are of the community of the believers. If Allah wills we shall join you.
Grade: Sahih

Hadith #3238 - Sunan Abi Dawud - Abu Da'ud أبو داود السجستاني الأزدي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ayoub al-Sakhtiyani أيوب السختياني; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sulaiman al-A'mash الأعمش / سليمان بن مهران; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
To the Messenger of Allah (ﷺ) was brought man wearing ihram who was thrown by his she-camel and has his neck broken and had died. He then said: Shroud him in his two garments, was him with water and lotus leaves, but do not cover his head, for he will be raised on the Day of Resurrection saying the talbiyah. Abu Dawud said: I heard Ahmad b. Hanbal say: There are five rules of the law (sunan) in this tradition: “Shroud him in his two garment,” that is, the dead should be shrouded in his two
Grade: Sahih

Hadith #3388 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Umar; Muhammad bin Kathir bin Abi 'Ata' محمد بن كثير بن أبي عطاء الثقفي; Rafi' bin Khadij bin Rafi'; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I Ammar, and Sa’d became partners in what we would receive on the day of Badr. Sa’d then brought two prisoners, but I and Ammar did not bring anything.
Grade: Da'if

Hadith #3416 - Sunan Abi Dawud - Amr bin 'Uthman عمرو بن عثمان بن عفان; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Junadah bin Abi Umayya; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Ubada bin As-Samit (Sunan Abi Dawud)
I taught some persons of the people of Suffah writing and the Qur’an. A man of them presented to me a bow. I said: It cannot be reckoned property; may I shoot with it in Allah’s path? I must come to the Apostle of of Allah (ﷺ) and ask him (about it). So I came to him and said : Messenger of Allah (ﷺ), one of those whom I have been teaching writing and the Qur’an has presented me a bow, and as it cannot be reckoned property, may I shoot with it in Allah’s path? He said: If you want t
Grade: Sahih

Hadith #3477 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Da'ud bin 'Abdur Rahman al-'Atar داود بن عبد الرحمن العطار; Iyas bin 'Abd al-Mazni; Siyar bin Salaama, Abu al-Minhal سيار بن سلامة الرياحي أبو المنهال (Sunan Abi Dawud)
A man from the immigrants of the Companions of the Prophet (ﷺ) said: I participated in battle three times along with the Prophet (ﷺ). I heard him say: Muslims have common share in three (things). grass, water and fire.
Grade: Sahih

Hadith #3496 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; ibn Abbas; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sulaiman bin Harb سليمان بن حرب; Tawus bin Kaysan طاوس; Wadah bin 'Abdullah al-Yashkari وضاح بن عبد الله اليشكري أبو عوانة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone buys grain, he should not sell it until he measures it. Abu Bakr added in his version: I asked Ibn ‘Abbas: Why ? He replied: Do you not see that they sell (grain) for gold, but the grain is still with the seller.
Grade: Sahih

Hadith #3558 - Sunan Abi Dawud - Abu Ja'far al-Nafaili عبد الله بن محمد أبو جعفر النفيلي الحران; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Tawus bin Kaysan طاوس; Zayd ibn Thabit (Sunan Abi Dawud)
The Prophet (ﷺ) said: Life-tenancy is lawful for the one to whom it is given and donation of property to go to the survivor is lawful to whom it is given.
Grade: Sahih

Hadith #3607 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hassan ibn Ali bin Abi Talib; ibn Abbas; Qays ibn Sa'd ibn 'Ubadah; Uthman bin Muhammad; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
The Prophet (ﷺ) bought a horse from a Bedouin. The Prophet (ﷺ) took him with him to pay him the price of his horse. The Messenger of Allah (ﷺ) walked quickly and the Bedouin walked slowly. The people stopped the Bedouin and began to bargain with him for the horse as and they did not know that the Prophet (ﷺ) had bought it. The Bedouin called the Messenger of Allah (ﷺ) saying: If you want this horse, (then buy it), otherwise I shall sell it. The Prophet (ﷺ) stopped when he heard the c
Grade: Sahih

Hadith #3608 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Muhammad Ibn Maslama; Salmah bin Shbyb سلمة بن شبيب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) gave a decision on the basis of an oath and a single witness.
Grade: Sahih

Hadith #3669 - Sunan Abi Dawud - Aabad bin Musa al-Khtly عباد بن موسى الختلي; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Isma'il bin Ja'far bin Abi Kathir إسماعيل بن جعفر بن أبي كثير الأنصاري; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Umar ibn al-Khattab (Sunan Abi Dawud)
The prohibition of wine came down when (the Quranic verse ) came down. It was made from five thing namely, grapes, dates, honey, wheat ,barley. Wine is what infects (khamara) the mind. There are three things I wished that the prophet (ﷺ) would not leave us until he explained them fully to our satisfaction: (share of) grandfather, one who leaves no descendants or ascendants as hairs, and the details of usury.
Grade: Sahih

Hadith #3787 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Jabir ibn 'Abdullah; Muhammad bin 'Ali b. al-Hussain al-Baqir محمد بن علي بن الحسين بن علي ,الباقر; Sulaiman bin Harb سليمان بن حرب (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) forbade riding the camel which feeds on filth and drinking its milk.
Grade: Sahih

Hadith #3799 - Sunan Abi Dawud - al-Fadl bin Dakayn, Abu Na'eem الفضل بن دكين أبو نعيم الملائي; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Saleem bin Aswad, Abu al-Ash'atha سليم بن أسود أبو الشعثاء المحاربي (Sunan Abi Dawud)
Numaylah said: I was with Ibn Umar. He was asked about eating hedgehog. He recited: “Say: I find not in the message received by me by inspiration any (meat) forbidden.” An old man who was with him said: I heard AbuHurayrah say: It was mentioned to the Messenger of Allah (ﷺ). Noxious of the noxious. Ibn Umar said: If the Messenger of Allah (ﷺ) had said it, it is as he said that we did not know.
Grade: Da'if

Hadith #3807 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hajjaj bin al-Minhal حجاج بن المنهال; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah (Sunan Abi Dawud)
that the Prophet (ﷺ) forbade payment for a cat. Ibn AbdulMalik said: to eat a cat and to enjoy its price.
Grade: Sahih

Hadith #3946 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
If a man emancipates his share in a slave, the rest will be emancipated by his money if he has enough money to pay the full price for him.
Grade: Sahih

Hadith #3973 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata' bin Abi Rabah عطاء بن أبي رباح; ibn Abbas; Muhammad bin 'Isa bin Hyan محمد بن عيسى بن حيان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I came in the deputation of Banu al-Muntafiq to the Messenger of Allah (ﷺ). He then narrated the rest of the tradition. The Prophet (ﷺ) said: la tahsibanna (do not think) and did not say: la tahsabanna (do not think).
Grade: Sahih

Hadith #3988 - Sunan Abi Dawud - Abu Hurairah; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ikrama عكرمة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Abi Dawud)
I came to the Prophet (ﷺ). He then narrated the rest of the tradition. A man from the people said: “Messenger of Allah! tell us about Saba’; what is it: land or woman? He replied: It is neither land nor woman; it is a man to whom ten children of the Arabs were born: six of them lived in the Yemen and four lived in Syria. The narrator Uthman said al-Ghatafani instead of al-Ghutayfi. He said: It has been transmitted to us by al-Hasan ibn al-Hakam an-Nakha’i.
Grade: Hasan Sahih

Hadith #3991 - Sunan Abi Dawud - Ahmad bin Hanbal أحمد بن حنبل; Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata' bin Abi Rabah عطاء بن أبي رباح; Safwan bin 'Amr bin Harm al-Saksaki صفوان بن عمرو بن هرم السكسكي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) read: “(There is for him) Rest and satisfaction” (faruhun wa rayhan).
Grade: Hasan

Hadith #4058 - Sunan Abi Dawud - Abdul Malik bin Mysrh عبد الملك بن ميسرة الزراد; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Jabir ibn 'Abdullah; Mas'ar bin Kadam مسعر بن كدام; Muhammad bin 'Abdullah bin al-Zubair محمد بن عبد الله أبو أحمد الزبيري; Nasr bin 'Ali bin Nasr bin 'Ali (Sunan Abi Dawud)
The word “siyara” means striped with silk.
Grade: Sahih

Hadith #4537 - Sunan Abi Dawud - Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Sufyan bin 'Uyaynah سفيان بن عيينة; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
‘Umar b. al-Khattab (ra) addressed us and said: I did not send my collectors (of zakat) so that they strike your bodies and that they take your property. If that is done with someone and he appeals to me, I shall take retaliation on him. Amr ibn al-‘As said: If any man (i.e. governor) inflicts disciplinary punishment on his subjects, would you take retaliation on him too? He said: Yes, by Him in Whose hand my soul is, I shall take retaliation on him. I saw that the Messenger of Allah (ﷺ) h
Grade: Hasan

Hadith #4538 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Abi Ghalb محمد بن أبي غالب القومسي; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The Prophet (ﷺ) Said: The disputants should refrain from taking retaliation. The one who is nearer should forgive first and then the one who is next to him, even if (the one who forgives) were a woman. Abu Dawud said: I have been informed that forgiving by women in the case of murder is permissible if a woman were one of the heirs (of the slain). I have been told on the authority of Abu ‘Ubaid about the meaning of the word yanhajizu, that is, they should refrain from retaliation.
Grade: Da'if

Hadith #4544 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ikrama عكرمة; Muhammad bin Abi Da'ud al-Bghdady محمد بن أبي داود; Muhammad Ibn Maslama; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Abi Dawud)
I read out to Sa’id b. Ya’qub al-Taliqini who said: Abu Tumailah transmitted to us, saying: Muhammad b. Ishaq transmitted to us saying: ‘Ata reported Jabir b. ‘Abd Allah as saying: The Messenger of Allah (ﷺ) fixed; and he mentioned the tradition like that of Musa; he said: And those who possess corn food should pay something which I do not remember.
Grade: Da'if

Hadith #4570 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Ibn Jurayj ابن جريج; Tawus bin Kaysan طاوس; Umar ibn al-Khattab (Sunan Abi Dawud)
‘Umar consulted the people about the compensation of abortion of woman. Al-Mughirah b. Shu’bah said: I was present with the Messenger of Allah (ﷺ) when he gave judgement that a male or female slave should testify you. So he brought Muhammad b. Maslamah to him. Harun added: He then testified him. Imlas means a man striking the belly of his wife. Abu Dawud said: I have been informed that Abu ‘Ubaid said: It (abortion) is called imlas because the woman causes it to slip before the time of d
Grade: Sahih

Hadith #4571 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
Hammad b. Zaid and Hammad b. Salamah transmitted it from Hisham b. ‘Arubah on his father’s authority who said that ‘Umar said…
Grade: Sahih

Hadith #4589 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Sa'id bin Sulaiman al-Dabi سعيد بن سليمان - سعدويه الضبي; Sulaiman bin Khatir al-'Abdi سليمان بن كثير العبدي; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Khalid with a different chain of narrators to the same effect.
Grade: Hasan

Hadith #4699 - Sunan Abi Dawud - Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Sufyan bin 'Uyaynah سفيان بن عيينة; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Tawus bin Kaysan طاوس (Sunan Abi Dawud)
I went to Ubayy b. Ka’b and said him : I am confused about Divine decree, so tell me something by means of which Allah may remove the confusion from my mind. He replied : were Allah to punish everyone in the heavens and in the earth. He would do so without being unjust to them, and were he to show mercy to them his mercy would be much better than their actions merited. Were you to spend in support of Allah’s cause an amount of gold equivalent to Uhud, Allah would not accept it from you till
Grade: Sahih

Hadith #4705 - Sunan Abi Dawud - Amr bin Dinar عمرو بن دينار الأثرم الجمحي; ibn Abbas; Muhammad bin Mhran محمد بن مهران; Sa'id bin Jubayr سعيد بن جبير الأسدي; Sufyan bin 'Uyaynah سفيان بن عيينة; Ubayy ibn Ka'b (Sunan Abi Dawud)
The boy whom al-Khidr had killed was created an infidel. Had he lived, he would have moved his parents to rebellion and unbelief.
Grade: Sahih

Hadith #4939 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Abi Dawud)
If anyone plays backgammon, he sinks his hand in the flesh of swine and its blood.
Grade: Sahih

Hadith #5130 - Sunan Abi Dawud - Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Hamam bin Munabbih همام بن منبه بن كامل; Sufyan bin 'Uyaynah سفيان بن عيينة; Wahb bin Munabbih al-Abnavi وهب بن منبه الأبناوي (Sunan Abi Dawud)
The Prophet (ﷺ) said: Your love for a thing causes blindness and deafness.
Grade: Da'if